2007
DOI: 10.4161/hv.3.1.3537
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Vaccination with Epidermal Growth Factor (EGF) in Advanced Lung Cancer: Analysis of Pooled Data from Three Clinical Trials

Abstract: KEy wordscancer vaccine, epidermal growth factor, non-small cell lung cancer AbbrEViATioNs AbsTrACTWe have undertaken the analysis of pooled data from three pilot clinical trials of vaccination with Epidermal Growth Factor (EGF) in patients with advanced non small cell lung cancer (NSCLC), addressing particularly the issue of the relationship between immunization and survival. Eighty-three patients with advanced disease were included in three pilot clinical trials and vaccinated with the EGF Vaccine. The tria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 14 publications
2
30
0
Order By: Relevance
“…Pooled data from three phase I/II randomized trials (n = 83, all of whom had had at least one line of conventional treatment) showed that, on average, vaccinated patients had a mean survival time of almost double that of concurrent unvaccinated controls (9.13 vs. 4.85 mo, p < 0.02). 4 A larger scale Phase II randomized controlled trial (n = 80) produced similar results. 5 It added that vaccinated patients under the age of 60 had an especially improved median survival time over control subjects (11.57 vs. 5.33 mo, p < 0.02).…”
Section: Introductionsupporting
confidence: 72%
See 4 more Smart Citations
“…Pooled data from three phase I/II randomized trials (n = 83, all of whom had had at least one line of conventional treatment) showed that, on average, vaccinated patients had a mean survival time of almost double that of concurrent unvaccinated controls (9.13 vs. 4.85 mo, p < 0.02). 4 A larger scale Phase II randomized controlled trial (n = 80) produced similar results. 5 It added that vaccinated patients under the age of 60 had an especially improved median survival time over control subjects (11.57 vs. 5.33 mo, p < 0.02).…”
Section: Introductionsupporting
confidence: 72%
“…Ongoing vaccination is necessary to boost antibody titers back to peak levels. 4 Therefore it is interesting that her disease has not shown progression after her last injection some 28 mo previously. Her age may be a contributing factor-54 y old at time of vaccine commencement.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations